UMP publisher's second journal indexed in Scopus database - Shalfarina, Shahriman (Penerbit UMP, 2014)

(untitled)
Kuantan, December 9:December was a fitting and sweetest month to end the year for Universiti Malaysia Pahang (UMP) Publisher and Faculty of Mechanical Engineering (FKM) when the Journal of Mechanical Engineering and Sciences (JMES) was successfully indexed in the SCOPUS database on December 10, 2014.